KOMUNIKASI NONVERBAL DALAM MEMBANGUN KOMUNIKASI EFEKTIF (STUDI KASUS PADA FRONTLINER BANK CENTRAL ASIA BATAM) - Kasmila, Mia; Abidin, Sholihul (LPPM Universitas Putera Batam, 2024)
This research discusses the use of nonverbal communication by Bank Central Asia (BCA) frontliners in Batam.The research results show that frontliners tend to use various forms of nonverbal communication, such as eyecontact, smiling, open body language, polite hand gestures, and an upright and confident body posture. Afriendly, calm and professional tone of voice is also considered important. The physical distance betweenfrontliners and customers is adjusted to cultural norms and personal preferences. BCA frontliners receivespecial training in nonverbal communication to improve their skills in interacting with customers. They realizethat their nonverbal communication can influence a company's image and appreciate the importance of makinga positive impression. Positive communication can create a pleasant experience, increase trust, and give theimpression that customers are valued. Frontliners who are skilled at nonverbal communication can influencecustomers' purchasing decisions and build strong emotional connections. Therefore, investment in developingthe nonverbal communication skills of frontliners at Bank Central Asia in Batam is considered to providebenefits for the company's long-term success